National Health Service Bill
1946-04 1946 1940s 10 pages - 6- FINANCE - [Sec. 52-56] 34. The Bill provides [Sec. 54(1) (a) (b)] that in the case of non-teaching hospitals monies shall be paid direct from the Exchequer to the Regional Board who will be given "as much financial freedom for local initiative and variety of enterprise as general principles of exchequer responsibility make possible" (White Paper, Para. 24). 35. The expenditure of the Regional Board is to include expenditure incurred by Local Hospital Management Committees in exercising functions on behalf of the Board. The expenditure of the Local Hospital Management Committee is therefore defrayed by the Regional Hospital Board. [Sec. 54(2)] This means that the entity and initiative of the Local Hospital Management Committee are completely absorbed within that of the Regional Board [White Paper, Para. 24]. 36. The position as regards the teaching hospitals differs and is dealt with below (Para. 44). 37. THE ASSOCIATION SUBMITS that these arrangements completely frustrate any effective function on the part of the Local Hospital Management Committee and are not therefore conducive to the provision by the individual hospital of an efficient service to its patients. The Association advocates financial arrangements in accordance with Para. 6 of its plan (attached herewith). The payment could best be made by means of block grant based on annual budget, and within this limitation the Local Hospital Management Committee should have freedom and control of its expenditure. TEACHING HOSPITALS 38. Section 11 (7) of the Bill extends the designation "Teaching Hospital" which at present is, by common usage, confined to hospitals training undergraduate medical students. 39. Some special administrative and financial arrangements proposed for the teaching hospitals have led many people to believe that they are in a position of special independence in relation to the scheme as a whole. This is quite erroneous. 40. The privileges accorded to them are power to appoint their own staff (which should be given to all hospitals) [Sec. 12 (3)7] a special place in relation to regional planning (which no one would deny them) [White Paper, Para. 22] power - which they are unlikely to be able to use - to attract further gifts and legacies; and finally their endowments are in some sense to be restored to them (but see Para. 43 below). 41. On the other hand they are to be taken over and owned by the Minister; their buildings and equipment, like that of all other hospitals, are confiscated and, as the White Paper (Para.28) says; "The fact that special arrangements may be made for them, does not mean that they are not to form an integral part of the hospital service as a whole." 42. Board of Governors. Though each Teaching Hospital or group is to have its own Board of Governors, the Board is to be constituted by the Minister [Sec. 11(7)]; on the new Board the representation of the existing trustees and Governors will be something less than 2/5ths, possibly less than 1/5th [Third Schedule, Part III]. 292/847/4/19